The use of consortia in the internationalization of construction firms – Mota-Engil study case - Silva, Susana Costa e (2011)
Paper also presented at: 2nd Annual Copenhagen Conference on Partnerships: crating innovative solutions through collaboration, Copenhagen, 17-18 November.